Intrinsic thalamocortical connectivity varies in the age of onset subtypes in major depressive disorder - Brown EC (Dove Medical Press, 2018)
Elliot C Brown,1–3 Darren L Clark,1–3 Stefanie Hassel,1,2 Glenda MacQueen,1,2 Rajamannar Ramasubbu1–3 1Mathison Centre for Mental Health Research and Education, University of Calgary, Calgary, AB, Canada; 2Department of Psychiatry, University of Calgary, Calgary, AB, Canada; 3Department of Clinical Neurosciences, University of Calgary, Calgary, AB, Canada Background: Differences in the thalamocortical system have been shown in patients with major depressive disorder (MDD). Given prior evidence of phenotypic heterogeneity by the age of onset in MDD, we examined whether differences in thalamocortical connectivity could identify biological subtypes of MDD defined by the age of illness onset. Methods: A total of 94 subjects including 20 early-onset (EO) MDD (onset, 18 years), 34 adult-onset (AO) MDD, and 40 healthy controls (HCs) underwent resting-state functional MRI. Blood-oxygen-level-dependent time courses were extracted from six cortical regions of interest (ROIs) consisting of frontal, temporal, parietal, and occipital lobes and precentral and postcentral gyri. Each ROI’s time course was then correlated with each voxel in thalamus, while covarying out signal from every other ROI. Results: The analysis of variance results showed significant main effects of group in frontal and temporal connectivity with thalamus. Group contrasts showed a right fronto-thalamic hypoconnectivity only in AO-MDD, but not in EO-MDD, when compared to HCs. However, direct comparison between EO-MDD and AO-MDD showed no differences. Furthermore, there was a right temporal–thalamic hyperconnectivity in both EO-MDD and AO-MDD patients relative to HCs. These results were not accounted for by sex, age, or illness burden. Conclusion: The age of illness onset may be a source of heterogeneity in fronto-thalamic intrinsic connectivity in MDD. Keywords: depression, age of onset, neuroimaging, thalamus, cortex, resting-state fMRI